Sorption behavior of zeolite P and its modified forms in the removal of selected hazardous metals and oxyanions from aqueous media - Tan, See Hua (2007)
Due to their toxicity and persistence, hazardous metal ions such as lead (Pb2+), cadmium (Cd2+) and zinc (Zn2+) as well as oxyanions like selenite, Se (IV) and selenate, Se (VI) pose a worrying threat to the environment and human health when released into water resources as constituents of waste. This study covers the synthesis, characterizations and analytical works on the development of an inexpensive and excellent inorganic sorbent, i.e. zeolite Na-P2 which was synthesized using local rice husk ash as the raw material. The product was well characterized with various sophisticated techniques and further modified into its nearly-homoionic sodium and calcium form zeolite through ion exchange in order to investigate the sorption behaviors of these cationic form zeolite samples towards the selected hazardous metal ions. The sorption of selected metals such as Pb2+, Cd2+ and Zn2+ was proven to be ion-exchange process through batch adsorption studies. The removal efficiencies of these zeolite species were investigated via several variables such as time, concentration, pH and competition within the solutes. The binary ion-exchange isotherms were constructed using thermodynamic equilibrium model and the standard free energies of exchange were calculated as well. The selectivity sequence of zeolite Na-P2 was as Pb2+>Cd2+>Na+>Zn2+ whereas for Caexchanged garronite which denoted as Homo-Ca, the selectivity sequence was Pb2+>Ca2+>Cd2+>Zn2+. The multicomponent exchange of zeolite was also investigated. On the other hand, the original zeolite Na-P2 was loaded with aluminium ions using aluminium sulfate post desilication in order to investigate its capability in the removal of selenite and selenate species in water. Different variables of the selenium species adsorption onto aluminium-loaded zeolite Na-P2 such as time, concentration and ionic strength were also studied. The results showed that the aluminium-loaded zeolite Na-P2 (sample 10Al-P) performed well in the removal of selenium oxyanions from water compared to other materials. As conclusion, zeolite Na-P2 and its modified forms can be used as excellent metal-removing agents in the water purification process